Cardiovascular prevention using WhatsApp, project "Family Health: Connected and Healthy" - Cristiano José Mendes Pinto; Fanuel Pedro de Puiz; Silvia Maria Ribeiro Oyama; Alberto Caldas Afonso; Bruno Caramelli (2021)
Objective: to analyze whether an educational program for cardiovascular prevention using WhatsApp can contribute to reducing Framingham risk score (FRS) among adults. Method: this is an intervention study, developed during one year (October/2019 to October/2020) in three public schools in São Paulo, among fathers, mothers, and family members of children enrolled in elementary school. Parents were invited to participate in the study by means of a note sent in the school agenda, and after signing the consent form, the participants received a weekly message from the researchers by WhatsApp, with guidelines to avoid sedentarism and maintain healthy lifestyle habits. Clinical and laboratory data were collected at the beginning and end of the study. Results: the study subjects were 70 adults, age 43.2 (±12 years), 47 females and 23 males. At the beginning of the study there were 09 (12.9%) parents with intermediate or high FRS, and at the end of the study there were 08 (11.4%) parents with intermediate or high FRS (p=0.79). A reduction in diastolic blood pressure was observed, mean from 80.3 mmHg to 77.7 mmHg (p=0.03; ±9.44), other three risk factors showed worsening in the outcome at the end of the study: HDL-cholesterol reduced mean from 55.9 mg/dL to 48.7 mg/dL (p=0.01), blood glucose increased from 91.4 mg/dL to 94.4 mg/dL (p=0.01) and body mass index was from 28.6 to 29.2 (p=0.01). Conclusion: The cardiovascular prevention education program using WhatsApp did not promote a reduction in FRS, and diastolic blood pressure was the only risk factor that responded to the intervention.